An Efficient Approach for Optimizing Frequency Reconfigurable Pixel Antennas Using Genetic Algorithms - Sichao Song; Murch, Ross D. (IEEE transactions on antennas and propagation, 2014)
In this paper we describe a method for optimizing frequency reconfigurable pixel antennas. The method utilizes a multi-objective function that is efficiently computed by using only one full electromagnetic simulation in the entire genetic algorithm optimization process. Minimization of the number of switches in the design is also attempted. The method is demonstrated using an antenna structure consisting of a rectangular grid of pixels adjacent to a ground plane and using RF MEMS switches for achieving the reconfigurability. The effects of the RF MEMS switches on the antenna performance as well as the control feed lines for them are also addressed. We provide both simulation and experimental results for a reconfigurable dual-band antenna that reconfigures the bands 820-1140 and 1720-1900 MHz to the bands 860-1160 and 1890-2300 MHz with dimensions of 39 mm × 24 mm on a ground plane of 40 mm × 65 mm with one switch only. The results demonstrate that reconfigurable antennas can be designed effectively with a minimum number of switches using an efficient optimization method.